2020
DOI: 10.1055/s-0040-1714413
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative MRI-guided Resection in Pediatric Brain Tumor Surgery: A Meta-analysis of Extent of Resection and Safety Outcomes

Abstract: Background The objective of this meta-analysis was to analyze the impact of intraoperative magnetic resonance imaging (iMRI) on pediatric brain tumor surgery with regard to the frequency of histopathologic entities, additional resections secondary to iMRI, rate of gross total resections (GTR) in glioma surgery, extent of resection (EoR) in supra- and infratentorial compartment, surgical site infections (SSIs), and neurologic outcome after surgery. Methods MEDLINE/PubMed Service was searched for the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…It is affording a specific focus on the non‐NF1 grade 1 PLGGs, where we confirmed that BRAF p.V600E had no impact on survival when tumors were completely resected. Therefore, similar to the more heterogeneous groups of grade 1 and 2 PLGGs that were published recently, our therapeutic management should tend in grade 1 to a near‐total resection using more and more intraoperative MRI to obtain a lower morbidity and have a safer outcome 33,34 . Our conclusions linking the presence of BRAF p.V600E in PLGGs or the worst patient outcome to a higher proportion of the solid components at MRI are leading to extend this surgical principle to all grade 1 PLGGs presenting a solid feature above 50% of the entire tumor at iMRI.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…It is affording a specific focus on the non‐NF1 grade 1 PLGGs, where we confirmed that BRAF p.V600E had no impact on survival when tumors were completely resected. Therefore, similar to the more heterogeneous groups of grade 1 and 2 PLGGs that were published recently, our therapeutic management should tend in grade 1 to a near‐total resection using more and more intraoperative MRI to obtain a lower morbidity and have a safer outcome 33,34 . Our conclusions linking the presence of BRAF p.V600E in PLGGs or the worst patient outcome to a higher proportion of the solid components at MRI are leading to extend this surgical principle to all grade 1 PLGGs presenting a solid feature above 50% of the entire tumor at iMRI.…”
Section: Discussionsupporting
confidence: 66%
“…33,34 Our conclusions linking the presence of BRAF p.V600E in PLGGs or the worst patient outcome to a higher proportion of the solid components at MRI are leading to extend this surgical principle to all grade 1 PLGGs presenting a solid feature above 50% of the entire tumor at iMRI. Correlations between cystic and solid proportions and the responses Abbreviations : N/A informations not avaliable; CR complete response; PR, partial response; SD, stable disease; PD, progressive disease / * 2 patients did not have FLAIR sequences / ** one patient with an optic pathway glioma progressed with multiple lesions.…”
mentioning
confidence: 88%
“…228 Another significant aspect of the ioMR imaging procedure concerns a possible increase in surgical site infection because craniotomy patients need to be moved into unsterilized diagnostic MR scanner. We were able to identify only two reports dealing with this issue, where it was noted that the rate of surgical site infection and the frequency of new neurologic deficits after ioMR image-guided surgery were within the normal range of pediatric neuro-oncologic surgery, 229 as well as wide age ranged (1-84 years old) at the multi-theater type system. 62 Overall, ioMR imaging seems to have improved the safety and increased the amount of tumor resected in patients with glioma, but the certainty of the evidence is low.…”
Section: Interstitial Chemotherapymentioning
confidence: 99%
“…Wach et al., in their metanalysis, evaluated the impact of iMRI on surgery of paediatric brain tumours by analysing data on the frequency of histopathologic entities, additional resections secondary to iMRI, rate of gross total resections in glioma surgery, and neurologic outcome after surgery. Overall, iMRI-guided surgery seems to improve paediatric glioma surgery, with a frequency of new neurologic deficits after iMRI-guided surgery within the normal range of paediatric neuro-oncologic surgery [ 73 ]. About brain tumour resection, Avula et al.…”
Section: New Intra-operative Devicesmentioning
confidence: 99%